Features of the composition and deformation of rock within the Marmarosh massif (in Ukraine) - Murovska, A.; Gintov, O.; Alokhin, V.; Ishkov, V.; Boiarska, A.; Mychak, S. (Kyiv, 2021)
Microscopic study of rocks from fault zones reveals different types of dynamometamorphic microstructures, which were formed under compression and shear conditions: micro boudinage, mylonitization, deformation bands, subparallel zones of intragranular microcracks, etc. Сhanges in the optical properties of minerals (wavy extinction of quartz), processes of recrystallization of minerals (quartz, calcite), deformational twinning (calcite), new formations of stress minerals (muscovite along the mylonitization zone) are described. All these phenomena are clearly linked with the deformation regimes of compaction and transpression reconstructed in the study area.
Keywords: dynamometamorphic microstructure; micro boudinage; mylonitization; intragranular microcrack